A sensitive and high throughput TaqMan-based reverse transcription quantitative polymerase chain reaction assay efficiently discriminates ALK rearrangement from overexpression for lung cancer FFPE specimens. (April 2016) - Lung, Jrhau; Lin, Yu-Ching; Hung, Ming-Szu; Jiang, Yuan Yuan; Lee, Kuan-Der; Lin, Paul Yann; Tsai, Ying Huang
Highlights: A sensitive and high throughput TaqMan based ALK qPCR assay was established. High concordance between qPCR, FISH and IHC based ALK tests. The qPCR assay can efficiently discriminate ALK rearrangement from overexpression. The qPCR assay helps clarify the discrepancies between ALK FISH and IHC results. Abstract: Objectives: ALK fusion gene is an oncogenic driver in lung cancer with low prevalence, which can be ameliorated by crizotinib. Currently, ALK fusion gene can be diagnosed by fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC), but inconstistnt results between the two methods are encountered regularly. To make the ALK fusion gene screening more efficient and to provide a simple solution to clarify the discrepancy between FISH and IHC results, a sensitive TaqMan-based reverse transcription quantitative polymerase chain reaction (RT-qPCR) assay was established. Materials and methods: The 3-plex TaqMan-based RT-qPCR assay was established and performed on 102 archived formalin-fixed, paraffin-embedded (FFPE) NSCLC samples to detect ALK rearrangement and overexpression. Break-apart FISH and automatic immunohistochemistry based ALK assays were performed side by side using tissue microarray. Results: The RT-qPCR was performed successfully for 80 samples and 10 of them showed positive signals. Three out of the 10 qPCR positive cases were further confirmed by FISH and IHC test. Two others were IHC positive and FISH negative, and expressed full-length ALK transcript. The rest were neither FISH nor IHC positive and their ALK expression level was significantly lower than those FISH or IHC positive cases. Conclusion: Our RT-qPCR assay demonstrates that the capability and reliability of ALK detection is comparable to FISH and IHC, but it is more effective at discriminating ALK rearrangement from overexpression. The RT-qPCR assay easily clarifies the discrepancy between FISH and IHC, and can be incorporated into routine ALK screening for lung cancer.